Ultrasound assessment of vasodilatory endothelial reactions in patients with Type 2 diabetes mellitus, associated with coronary heart disease and arterial hypertension - Ya. V. Evseeva; T. E. Kurilskaya; A. A. Runovich (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To assess heterogeneous vasodilatation mechanisms in coronary heart disease (CHD) patients with Type 2 diabetes mellitus (DM2) and arterial hypertension (AH). Material and methods. In total, 62 DM2 patients aged 41-60 years were examined. By DM2 compensation, all participants were divided into two groups: Group I (n=37) with compensated DM2, and Group 2 (n=25) with DM2 decompensation. Age- and gender-matched control group consisted of 30 relatively healthy volunteers. Endothelium-dependent vasodilatation (EDVD) of brachial artery (BA) was measured by ultrasound scanning and flow dopplerography, in reactive hyperemia test. Shear stress and endothelium sensitivity to shear stress were calculated. Endothelium-independent vasodilatation (EIVD) was assessed in sublingual nitroglycerin test. Results. In decompensated DM2 patients, even at rest, BA blood flow and elasticity were reduced. In Celermajer D.S. test, BA diameter increase was twice as low as in healthy individuals. Shear stress endothelial sensitivity was reduced in DM2 participants. In diabetic patients with carotid atherosclerosis, BA diameter increase in nitroglycerine test was significantly lower than in participants without peripheral artery atherosclerosis. Conclusion. In DM2 patients, atherogenic lipid metabolism disturbances resulted in reduced endothelial sensitivity to shear stress, and endothelial dysfunction in middle-size arteries. In inadequate hyperglycemia compensation, endothelial dysfunction was observed more often.